Phage therapy against methicillin-resistant Staphylococcus pseudintermedius: a novel strategy for canine pyoderma - Feng, Xiancheng; Du, Qingjie; Wang, Keyi; Chen, Ruiqi; Ma, Rui; Xing, Yunping; Lei, Xinyue; Wang, Miao; Dai, Pengxiu; Zhang, Xinke (Frontiers in Microbiology, 2026)
IntroductionMethicillin-resistant Staphylococcus pseudintermedius (MRSP) poses a major public health challenge due to its multidrug resistance. Phages represent an innovative therapeutic strategy with considerable potential against drug-resistant bacterial infections.MethodsIn this study, dogs clinically diagnosed with pyoderma were recruited to establish an epidemiological dataset, and multidrug-resistant S. pseudintermedius strains (including 6 MRSP isolates) were obtained from bacterial cultures. Three high-efficiency lytic phages were isolated using these MRSP strains as hosts and characterized. The combined efficacy of phages and antibiotics was evaluated in a pyoderma model via clinical scoring, histopathological examination, and tissue bacterial load quantification.ResultsNotably, these phages enhanced MRSP susceptibility to antibiotics, with genomic and proteomic analyses identifying key mediators of phage-mediated S. pseudintermedius lysis. The phage-antibiotic combination exhibited the most significant therapeutic effect on pyoderma, followed by the phage-only group. In contrast, the antibiotic-only group showed no significant improvement compared to the control group, with both yielding poor outcomes.DiscussionThis study provides a promising therapeutic strategy for the clinical management of canine pyoderma in veterinary medicine and offers valuable insights for safeguarding public health security.